Negotiating economic development : identity formation and collective action in Belize - Medina, Laurie Kroshus, 1962- (University of Arizona Press, 2004)
"Laurie Kroshus Medina analyzes the development of the citrus industry in Belize over fifteen years to explore the relationship between the production of collective identities and the negotiation of development policies at the interface of global and local processes. She shows how citrus farmers and workers, processing companies, and politicians compete to construct shared identities, now they mobilize collective actors, and how their collective action shapes the goals, policies, and practices associated with development." "Medina's research demonstrates how collective agency in Belize has pushed the citrus industry's development in directions that simultaneously conform to and diverge from the trajectories laid out by foreign agencies. Negotiating Economic Development provides a bridge from old to new studies of Latin American social movements as it offers key insights into competing forms of identity for a wide range of social scientists concerned with the human and social aspects of development issues and globalization."--Jacket.